2011
DOI: 10.1258/jhsrp.2010.010013
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Respiratory Admissions: Influence of Practice, Population and Hospital Factors

Abstract: Practice population, geographic and hospital supply factors are consistently associated with asthma and COPD admissions. Higher smoking rates among such patients in a practice are associated with higher admission rates. There is little evidence from this study that other modifiable general practice factors are important in influencing admission rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 19 publications
1
51
3
Order By: Relevance
“…In studies of the UK Quality and Outcomes Framework, in which incentives were directly tied to measured quality of care, any observed decreases in hospital admissions accompanying observed changes in quality were small, [25][26][27] and some studies found no association between measured quality and hospital admissions. 28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs. 24,[30][31][32][33][34] Studies of Ontario's pay-forperformance initiatives showed modest improvements in delivery of some preventive services 35,36 and no change in management of patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of the UK Quality and Outcomes Framework, in which incentives were directly tied to measured quality of care, any observed decreases in hospital admissions accompanying observed changes in quality were small, [25][26][27] and some studies found no association between measured quality and hospital admissions. 28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs. 24,[30][31][32][33][34] Studies of Ontario's pay-forperformance initiatives showed modest improvements in delivery of some preventive services 35,36 and no change in management of patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…39 Most research in this area focuses on care for individual diseases, using the delivery of specific services as indicators of quality. 24,[30][31][32][33][34] Evidence of the effect of incentive-based programs on broader outcomes such as access to primary care, continuity of care, 40 hospital admissions [25][26][27][28][29]41,42 and overall resource use 30,34,43 has been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have explored the factors affecting emergency admission rates overall, or for specific conditions, through studying variation between general practices in the UK [10][11][12][13][14][15][16][17][18][19] and internationally, 20 commissioning organisations in the UK 12,[21][22][23] or hospitals internationally. 24,25 Factors explaining variation were related to the population, particularly in terms of deprivation and health ( Table 1).…”
Section: Factors Affecting Emergency Admissionsmentioning
confidence: 99%
“…Much of the focus on health service-related factors affecting variation in emergency admissions has been on primary care ( Table 2), for example the quality and supply of, 10,12,14,17 and access to, primary care. 10,12,15,16 There is some evidence that factors within hospitals can affect emergency admissions, such as bed numbers and availability, 16 physical space 24 and clinical decision-making. 25 Research has also been undertaken on factors affecting variation in use of a common gateway to emergency admission -EDs.…”
Section: Factors Affecting Emergency Admissionsmentioning
confidence: 99%
“…4,12,13 This study contrasts with the findings of other research that reported decreased emergency admission with increasing distance from hospital and with higher deprivation. [31][32][33] The study differs from those in that a multilevel analysis was used clustering at the primary care trust level. The study concurs with others that reported increased emergency admissions with an increasing proportion of the population who are white.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%